Efficient degradation of neomycin by Bacillus velezensis and Cupriavidus basilensis isolated from mangrove soil and pharmaceutical wastewater - Yang, Qian; Huang, Wenzhuan; Yan, Xue; Ding, Qiang; Liu, Jiaxin; Cheng, Bo; Duan, Tao (Frontiers in Microbiology, 2025)
Neomycin, an aminoglycoside antibiotic, is widely utilized for veterinary medicine in disease prevention. Biodegradation is a key pathway for the removal of neomycin from the environment. To date, only the white-rot fungus Trametes versicolor and the ericoid mycorrhizal fungus Rhizoscyphus ericae have been documented to efficiently degrade neomycin. However, no bacterial species with neomycin-degrading capabilities have been reported, underscoring a significant gap in microbial research related to neomycin remediation. In this study, Cupriavidus basilensis and Bacillus velezensis were isolated from pharmaceutical wastewater and neomycin-free mangrove soil through enrichment culture and gradual acclimatization, respectively. These isolates demonstrated neomycin degradation rates of 46.4 and 37.6% in 96 h with 100 mg·L−1 neomycin as the sole carbon source. Cupriavidus basilensis achieved a degradation rate of 50.83% with ammonium sulfate supplementation, while Bacillus velezensis exhibited a superior degradation efficiency of 58.44% with soluble starch. Our findings offer valuable insights into the microbial degradation of neomycin. Two neomycin-degrading bacteria were isolated for the first time. Both species degraded neomycin as the sole carbon source or under co-metabolic conditions within 4 days. Microorganisms from neomycin-free environments adapted to neomycin stress and outperformed those from contaminated sources. This challenges the assumption that antibiotic-degrading microorganisms mainly originate from polluted environments. The findings expand the diversity of known neomycin-degrading microorganisms and demonstrate their potential for removing refractory neomycin from pharmaceutical wastewater.